Peran kepala sekolah dalam implementasi manajemen peningkatan mutu berbasis sekolah SD Negeri Ngawen III Kecamatan Ngawen Kabupaten Gunungkidul tahun pelajaran 2014/2015 - Kastono Kastono (Wiyata Dharma: Jurnal Penelitian dan Evaluasi Pendidikan, 2016)
This research aims to know the role of headmaster in teaching management; curriculum management; workforce management; equipment management; financial management; student service; public relations, and school climate management, and the relation with school-based quality improvement’s management at SD Negeri Ngawen III Kecamatan Ngawen Kabupaten Gunungkidul. This research is a descriptive-analytic non-statistic research by using a qualitative approach. The data are obtained from informants consist of headmasters, teachers, students, and chairman of school committee from observation results and documents. The data are analyzed using interactive analysis through three activities that are data reduction, data presentation, and conclusion. The data validity is obtained from the extension of participation and data triangulation. Generally, the role of headmaster in teaching management; curriculum management; workforce management; equipment management; financial management; student service; public relations, and school climate management, and the relation with school-based quality improvement’s management at SD Negeri Ngawen III Kecamatan Ngawen Kabupaten Gunungkidul are good implemented. Although there are temporary teachers with minimal welfare and unclear future career because of the wise leadership from the headmaster, the quality improvement’s management can work well.